Filsafat Manusia Dalam Teks Tutur Raré Angon - Dewi Yunairi; I Ketut Donder; I Gusti Putu Gede Widiana (Jurnal Penelitian Agama Hindu, 2019)
This research was conducted based on the author's interest towards the science of human philosophy. In this research the author appoint human philosophy inside one of the Balinese text named Tutur Raré Angon, because of the teachings contained are very important and interesting to do research, preserved and passed on to the next generation of Hindus. The nature of being human is very important, after knowing that, the readers will be more undertand about what to do to be a qualified person. This research can improve Hinduism's understanding of human concepts in Hindu literature through Tutur Raré Angon's texts. There are three issues discussed in this study, namely : 1) Human Existence In the text of Tutur Raré Angon's (2) Epistemic Structure In the text of Tutur Raré Angon's (3) Moral Aspects in Tutur Raré Angon's text. This study is a descriptive qualitative text or manuscript research. The primary data source in this study is the text of Tutur Raré Angon's. Data collection is done using the reading and writing techniques and literature study. The collected data is then analyzed using descriptive techniques, structural analysis, and text interpretation. The results of data analysis are presented in the form of descriptions. The results of this study are human existence in the text of Tutur Raré Angon's including (1) individuals and (2) religious. The epistemic structure in the Tutur Raré Angon text includes (1) Belief, (2) Truth and (3) Humans gain knowledge. Human morality in Tutur Raré Angon's texts includes (1) Goodness, Relationship with fellow humans and (3) Moral with nature.